2016
DOI: 10.1111/1365-2656.12509
|View full text |Cite
|
Sign up to set email alerts
|

Beyond neutral and forbidden links: morphological matches and the assembly of mutualistic hawkmoth–plant networks

Abstract: A major challenge in evolutionary ecology is to understand how co-evolutionary processes shape patterns of interactions between species at community level. Pollination of flowers with long corolla tubes by long-tongued hawkmoths has been invoked as a showcase model of co-evolution. Recently, optimal foraging models have predicted that there might be a close association between mouthparts' length and the corolla depth of the visited flowers, thus favouring trait convergence and specialization at community level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
117
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(124 citation statements)
references
References 52 publications
(146 reference statements)
7
117
0
Order By: Relevance
“…However, the increased mismatch between pollinator and flower traits due to the loss of long-tongued pollinators might diminish reproductive success in some long-tubed flowers. Across our study sites, pollinators generally preferred flowers with floral tubes that matched their proboscis (figures 3a, 4, and 5), in agreement with previous studies that suggested morphological matching between proboscis length and nectar holder depth in a Mediterranean pollination community [43] and a South American flower-hawkmoth community [54], and floral niche partitioning between short-and long-tongued bumblebees [18,55]. In high RBLP conditions, each pollinator functional group had two marked peaks in visit rate relative to corolla tube length that showed limited overlap with the peaks of other groups ( figure 5).…”
Section: Discussionsupporting
confidence: 91%
“…However, the increased mismatch between pollinator and flower traits due to the loss of long-tongued pollinators might diminish reproductive success in some long-tubed flowers. Across our study sites, pollinators generally preferred flowers with floral tubes that matched their proboscis (figures 3a, 4, and 5), in agreement with previous studies that suggested morphological matching between proboscis length and nectar holder depth in a Mediterranean pollination community [43] and a South American flower-hawkmoth community [54], and floral niche partitioning between short-and long-tongued bumblebees [18,55]. In high RBLP conditions, each pollinator functional group had two marked peaks in visit rate relative to corolla tube length that showed limited overlap with the peaks of other groups ( figure 5).…”
Section: Discussionsupporting
confidence: 91%
“…Sazatornil et al . () extend those results to the scale of the whole moth–plant assemblage and demonstrate that trait matching successfully predicts the diversity of interactions recorded. Interestingly enough, the interaction patterns in two local assemblages from ecotone areas of the Argentinian Chaco woodland–Yungas montane rain forest transition are better fitted by a neutral model where pairwise interactions are driven by probability of interspecific encounter.…”
supporting
confidence: 65%
“…Recent work by Sazatornil et al . () provides evidence that the types of trait mismatching outlined in Fig. limit the ranges of host plants for sphingid pollinators, and ultimately shape their complex plant–pollinator networks.…”
mentioning
confidence: 96%
“…This positive effect of encounter probability was not consistent with that presented by Olito and Fox (2015) for plant-pollinator interactions, but agrees with other studies showing neutrality as an important predictor of species assemblages, together with niche processes following the continuum theory (Gravel et al, 2006;Krishna et al, 2008;Vázquez et al, 2009;Kaiser-Bunbury et al, 2014). Most of these studies (mainly on plant-pollinator interactions) disentangled the mechanisms behind the macroscopic, global features of interaction networks (Trøjelsgaard and Olesen, 2016), but failed when seeking to predict pairwise interactions (Vázquez et al, 2009;Vizentin-Bugoni et al, 2014;Gilarranz et al, 2015;Sazatornil et al, 2016). Here we found it to work on the individual interaction scale.…”
Section: Consistency In the Mechanisms Determining Pairwise Interactionssupporting
confidence: 53%
“…It is generally agreed that both neutral and niche-driven processes contribute to the occurrence of pairwise mutualistic interactions and network structure (Bartomeus et al, 2016;García, 2016;González-Varo and Traveset, 2016;Sazatornil et al, 2016). That is, whether or not two species interact can be thought of as the result of two sequential processes.…”
Section: Introductionmentioning
confidence: 99%